Which is better, EGFR-TKI mono or combination for non-small cell lung cancer with mutated EGFR? - Tanzawa, Shigeru; Ishihara, Masashi; Haruyama, Terunobu; Ochiai, Ryosuke; Sakamoto, Takahiko; Honda, Takeshi; Ota, Shuji; Ichikawa, Yasuko; Watanabe, Kiyotaka; Seki, Nobuhiko (Translational Cancer Research, 2019)
Currently, three strategies for primary treatment of advanced non-small cell lung cancer (NSCLC) with EGFR gene mutations are being investigated: epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) monotherapy, EGFR-TKI + vascular endothelial growth factor (VEGF) inhibitor combination, and EGFR-TKI + cytotoxic anticancer agent combination (Tables 1,2).